The Development of 2D Animation on Raw Food Consumption - สอนสนธิ์ เจนจิรา; สีใหม่ ทัตพิชา; วัชรพฤกษาดี อมรวิทย์ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This research aimed to (1) study the safety of consuming raw or fermented foods, (2) study the process of creating animation media for public relations purposes, and (3) evaluate the satisfaction of the animation media for public relations purposes among a sample group of 30 Students from the Faculty of Information Technology and Digital Innovation. selected by accidental sampling. The research instruments included the 2D animation titled "Raw Food" and a satisfaction questionnaire. The statistical methods used to analyze the data were a 5-level rating scale (Likert Scale), mean, and standard deviation. The research findings showed that: (1) Content satisfaction evaluated by subject matter experts was at the ’Highest’ level (x̄= 4.60, S.D. = 0.47); (2) Media satisfaction evaluated by media specialists was at a ’High’ level (x̄= 4.00, S.D. = 0.73); (3) Content satisfaction evaluated by the 30 participants was at the ’Highest’ level (x̄= 4.61, S.D. = 0.63); and (4) Media satisfaction evaluated by the 30 participants was at a ’High’ level (x̄= 4.45, S.D. = 0.78).